OBEDIENCE OF CONTROL AND THE LEVEL OF BLOOD SUGAR IN KEDIRI BAPTIS HOSPITAL - Suprihatin, Suprihatin (Jurnal Penelitian STIKES Kediri, 2012)
Â Obedience controls carried out someone who suffers from a disease that requires control or check at the hospital. If the patient is less obedience will affect blood sugar levels. The purpose of this study to analyze compliance with the control of blood sugar levels at Baptist Hospital Kediri. The study design was cross-sectional. The population were patients with diabetes mellitus who controls or checks at Baptist Hospital Kediri. The sample of 81 respondents who met the inclusion criteria using accidental sampling. The independent variables was obedience control and the dependent variable was compliance control blood sugar levels. Data were collected using questionnaires and observation sheets laboratory using glukocard tool. The statistical test used